Dari “Diislamkan” ke “Dipestakan”: Pergeseran Makna Mujêlisên (Khitanan) pada Masyarakat Gayo - Indra Setia Bakti; Harinawati Harinawati; Siti Ikramatoun (Program Studi Sosiologi Agama Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri Ar-Raniry, Banda Aceh, Indonesia, 2021)
This study aims to describe the meaning shift of mujêlisên in Gayo society. The meaning given to the mujêlisên tradition has not been constant at all times. In the Gayo lens traditional, mujêlisên means something Islamic or